The efficacy of conservative therapy in patients with acute hemorrhoids: results of a subgroup analysis of the Russian population in the international study CHORALIS - Yu A. Shelygin; I. V. Kostarev; B. B. Kvasnikov; A. E. Pavlova; O. Zh. Linnik (Koloproktologia, 2026)
AIM: to obtain data from routine clinical practice on the effectiveness of conservative treatment for patients with acute hemorrhoids, in terms of its impact on symptom severity and quality of life. P ATIENT S AND METHODS: the international, observational, prospective CHORALIS study included adult outpatients with complaints characteristic of acute hemorrhoids and who received conservative treatment in accordance with routine clinical practice. The study was conducted in 9 countries: China (n = 268), Hungary (n = 71), Kenya (n = 22), Nigeria (n = 902), Russia (n = 500), Saudi Arabia (n = 200), Senegal (n = 662), Ukraine (n = 679), and Vietnam (n = 202), allowing for data to be analyzed from multiple regions of the world. This subgroup analysis includes treatment outcomes for patients enrolled in the study in the Russian Federation (RF). Treatment efficacy was assessed based on patient assessment of acute hemorrhoid symptom reduction using a visual analog scale (VAS) and patient questionnaires using the Clinical Global Impression (PGI-C) scale and the hemorrhoid-specific quality of life questionnaire (HEMO-FISS-QoL). RESULT S: the study in the Russian Federation included 500 patients (52.2% women), with a mean age of 41.1 ± 12.6 years. The most common symptoms were pain: 420/496 (84.6%), discomfort 477/496 (96.2%) and swelling in the anal area 352/496 (71.0%). Conservative treatment included the prescription of laxatives, topical agents and venoactive drugs: 440/499 (88.3%) received micronized purified flavonoid fraction (MPFF) preparations, and 58/499 (11.6%) diosmin. Over 4 weeks of treatment, the mean number of symptoms (IQR) decreased from 4 (3; 5) to 1 (0; 2), p < 0.001. Therapy based on venoactive drugs reduces pain intensity: initially, the median level was 5 (3.0; 7.0), and after 4 weeks — 1.2 (1.0; 2.0). The intensity of discomfort was moderate at baseline 5 (4.0; 7.2), and by the end of the observation period 1.5 (1.0; 2.0), p < 0.001 for lower symptoms. Nominally, the reduction in the number of patients with pain after 4 weeks in the MPFF group and the diosmin group was as follows: 84/438 (19.2%) and 20/57 (35.1%), respectively. The treatment provided constant self-sensitivity according to the PGI-C scale, limiting the time to improvement in 96.4% of patients, which led to satisfaction with the treatment of both the physician and the patient. CONCLUSION: in a subgroup analysis of data from the CHORALIS study, conducted in a population of Russian patients with acute hemorrhoids, conservative therapy based on the use of venoactive drugs (mostly MPFF) was effective in reducing the symptoms of acute hemorrhoids and improving quality of life.